The Psychometric Hepatic Encephalopathy Score for Diagnosis of Minimal Hepatic Encephalopathy in Liver Cirrhosis Patient - Cokorde Istri Yuliandari Krisnawardani Kumbara; I Dewa Nyoman Wibawa; I Gde Raka Widiana (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
Introduction: The psychometric hepatic encephalopathy score (PHES) is a tool that can be considered as a gold standard for detecting minimal hepatic encephalopathy (MHE) in liver cirrhosis patients. The PHES must be standardized based on the local healthy population before it can be used. The purpose of this study is to standardize the PHES with Indonesian local populations and set the cutoff point of PHES so it can be used to detect MHE in liver cirrhosis patients.